Characterisation of the ability of globulins from legume seeds to produce cocoa specific aroma - Sukor, Rashidah; Selamat, Jinap; Saari, Nazamid; Bakar, Jamilah (Universiti Putra Malaysia Press, 2007)
This study was carried out to extract and compare the characteristic ability of globulins from cottonseed, alfalfa seed, pea seed, mung bean and French bean with cocoa seeds to produce cocoa-specific aroma precursors. The extracted globulins were compared through SDS PAGE, amino acid and oligopeptide profiles. A very low recovery was obtained during globulin extraction from different seeds ranging from 0.5% to 2.7%. Cottonseed produced the highest total protein (13.90 mg/g), followed by cocoa seed (11.91 mg/g), whereas alfalfa seed, mung bean, pea seed and French bean produced 7.86, 4.77, 4.59 and 3.89 mg/g respectively. Two distinctive bands of 51.1 and 33.0 kDa were observed for cocoa vicilin-class globulin (VCG) from SDS PAGE. More than three bands were shown for other seed globulins. Comparative HPLC analyses of the obtained peptide mixtures revealed different and complex patterns of predominantly hydrophobic peptides. A similar high content of amides (glutamic acids-glutamine, aspartic acid- asparagine and arginine) and low concentrations of lysine were observed in all seeds globulin.